National philology, imperial hierarchies, and the 'Defective' book of Sir John Mandeville - White, T (Oxford University Press, 2019)
This article examines when and how the ‘Defective’ version of the Book of Sir John Mandeville came to be called ‘defective’. It describes the use of this name by Sir George F. Warner in an edition produced in 1889 for the elite bibliographic society the Roxburghe Club. Drawing on recent work in disability studies, it argues that the philological use of ‘defective’ be read in conjunction with its broader use in the elaboration of hierarchies of class, race, and gender. Far from a neutral descriptor, ‘defective’ provides a compelling example of the imbrication of medieval studies, imperialism, and Social Darwinist principles in the late nineteenth century. The article closes with the call not only to rename the ‘Defective’ version the ‘Common’ version, but also for a broader reappraisal of this apparently discrete version of Mandeville’s Book. However, it also argues that amid the increasing marketisation of higher education and the concomitant insecurity of academic labour, digital editing does not provide a straightforward answer to the question of how best to map and display the complex textual history of Mandeville’s Book.